2015
DOI: 10.1371/journal.pone.0124921
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmogenic Biophysical Phenotype for SCN5A Mutation S1787N Depends upon Splice Variant Background and Intracellular Acidosis

Abstract: Background SCN5A is a susceptibility gene for type 3 long QT syndrome, Brugada syndrome, and sudden infant death syndrome. I Na dysfunction from mutated SCN5A can depend upon the splice variant background in which it is expressed and also upon environmental factors such as acidosis. S1787N was reported previously as a LQT3-associated mutation and has also been observed in 1 of 295 healthy white controls. Here, we determined the in vitro biophysical phenotype of SCN5A-S1787N in an effort to further assess its p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…When compared with non-failing adult human heart, there were no differences in total SCN5A , SCN5A-6 , or SCN5A-6A expression ( Figure S3 B). We also investigated several common polymorphisms in SCN5A that are known to result in gain or loss of function, depending on the presence of other genetic mutations ( Ackerman et al., 2004 , Cheng et al., 2011 , Hu et al., 2015 , Kapplinger et al., 2015 , Makielski et al., 2003 , Shinlapawittayatorn et al., 2011 , Ye et al., 2003 ). We tested the four most likely polymorphisms S524Y, H558R, 1077del, or R1193Q.…”
Section: Resultsmentioning
confidence: 99%
“…When compared with non-failing adult human heart, there were no differences in total SCN5A , SCN5A-6 , or SCN5A-6A expression ( Figure S3 B). We also investigated several common polymorphisms in SCN5A that are known to result in gain or loss of function, depending on the presence of other genetic mutations ( Ackerman et al., 2004 , Cheng et al., 2011 , Hu et al., 2015 , Kapplinger et al., 2015 , Makielski et al., 2003 , Shinlapawittayatorn et al., 2011 , Ye et al., 2003 ). We tested the four most likely polymorphisms S524Y, H558R, 1077del, or R1193Q.…”
Section: Resultsmentioning
confidence: 99%
“…The dramatic increased late I Na found for SCN5A-N406K is typical of LQT3 [20]. The persistent Na current during action potential plateau is due to the failure of fast Na channel inactivation [8].…”
Section: Discussionmentioning
confidence: 99%
“…109 Other groups have shown that certain long QT type 3 syndrome mutations are more sensitive to intracellular acidosis than others. 111 Another environmental factor modulating the Na C channel is body temperature. In healthy humans, without underlying mutations in Na v 1.5 or other conditions, temperature-dependent cardiac abnormalities may occur in extreme hyperthermia but seldom when they experience a mild fever.…”
Section: Environmental Regulation Of Inactivationmentioning
confidence: 99%